Pengaruh Kualitas Pelayanan dan Komunikasi Interpersonal terhadap Kepuasan Mahasiswa dan Alumni: (Studi Kasus: Universitas Gunadarma) - Didit Tri Gunawan; Dimas Radhitio Atmohadikusumo; Dyan Tanjung Gunotomo (Universitas Veteran Bangun Nusantara, 2024)
This research aims to examine the influence of service quality and interpersonal communication at the diploma and transcript counter on the satisfaction of Gunadarma University students and alumni for the 2023-2024 period and to find out which has the most dominant influence on the satisfaction of Gunadarma University students and alumni. The data collection method was carried out through distributing online questionnaires and direct questionnaires to respondents. The data obtained was then processed using SPSS version 24 tools. This analysis includes descriptive analysis, validity test, reliability test, correlation test, multiple linear regression test, hypothesis test and coefficient of determination test. The results of this research are that Service Quality and Interpersonal Communication at the Diploma and Transcript counters affect Student and Alumni Satisfaction, Service Quality has no effect on Student and Alumni Satisfaction, and Interpersonal Communication simultaneously has a significant influence on Gunadarma University Student and Alumni Satisfaction for the 2023-2024 Period.